Augmented Reality Book Pengenalan Perangkat Gamelan Bali - Yostab Mariyantoni, I Kadek; Crisnapati, Padma Nyoman; Mahendra Darmawiguna, I Gede; Windu Antara Kesiman, Made (Universitas Pendidikan Ganesha, 2013)
Balinese gamelan are being abandoned by teenagers, one of contributing factor is the development of technology. The destination of this research is to utilize technology in a way to develop applications that can be used as a media for learning and introduce Balinese gamelan instruments with a more interactive and interesting. The research method used is the research and development, to develop an Augmented Reality Book application for introduction the Balinese gamelan instrument, using the waterfall model until the system testing phase. This application uses library vuforia that can be play a sound and display 3D objects Balinese gamelan instruments in a real environment with the help of books and android smartphones. The final result is a book that contains information and images related to Balinese gamelan (specially gong kebyar) which functioned as a marker and also Augmented Reality Book application android based device that is capable of displaying objects gamelan gong kebyar in 3-dimensional form just above the marker complete with the sound of the device gamelan and voice narration explanation. This application can be used as a media to introduce and preserve the national culture.